A1.70 Sterile inflammation occurs in a TLR9-independent manner in experimental arthritis and rheumatoid arthritis. (31st January 2014) - Mussard, Julie; Ribon, Matthieu; Clavel, Gaëlle; Boissier, Marie-Christophe; Decker, Patrice
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is an inflammatory disease of unknown etiology. Toll-like receptor (TLR) 9 recognizes pathogen-derived DNA and even self DNA under certain circumstances. Interestingly, environmental factors and especially bacterial infections have been suggested to favour RA development. In addition, TLR9 might also recognize damage-associated molecular patterns (DAMP) in RA. However, the involvement of TLR9 in RA remains unclear. Therefore, we have investigated whether TLR9 is necessary for disease development in a mouse model of RA and we analysed TLR9 expression in human samples. Materials and Methods: Disease development was followed in the collagen-induced arthritis (CIA) mouse model. The impact of TLR9 was evaluated by comparing wild-type (WT) mice and TLR9-knockout (KO) true littermates. Arthritis was followed by clinical score evaluation. Inflammation and bone destruction were estimated by histology. Anti-collagen antibody and blood cytokine levels were measured by ELISA. B and T lymphocytes as well as neutrophils were analysed by flow cytometry. Osteoclastogenesis was analysed by culturing bone marrow cells with M-CSF and RANKL and then counting TRAP-positive multinucleated cells by microscopy. Moreover, TLR9 expression was analysed ex vivo by flow cytometry on whole blood from healthy donors and RA patients. Results: TLR9 is not required for arthritis development in CIA as TLR9-KO mice strongly developed clinical arthritis. Accordingly, WT and KO mice produced similar levels of anti-collagen antibodies. As a control, we verified that WT and KO mice responded to complete Freund's adjuvant. Moreover, inflammation and joint destruction were observed in both WT and TLR9-KO mice. In agreement with those observations, no statistically significant difference was noted between WT and KO mice regarding the percentage or the activation of lymphocytes and neutrophils in the blood, spleen and lymph nodes. The impact of TLR9 on cytokine secretion and osteoclastogenesis in vivo is presently being analysed. In human samples, we have shown that leukocytes from healthy donors and RA patients express TLR9 at the same extent. Conclusions: TLR9-KO mice clearly develop arthritis. Immune cells from RA patients do not over-express TLR9 in comparison to healthy donors. Our results thus suggest that TLR9 does not play a crucial role in inflammatory arthritis development in the CIA model and that in vivo TLR9 ligands do not up-regulate TLR9 in RA patients. This also suggests that TLR9 is not strongly involved in the recognition of DAMP in RA.